2021
DOI: 10.3390/su13084352
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the Sustainability of a Real Estate Project Using Multi-Criteria Decision Making

Abstract: Today, sustainability, sustainable development and clean environment come to the fore worldwide. Consequently, the concept of sustainability has been introduced in project management. Sustainability issues have gained particular attention in the real estate sector. However, despite the fact that this sector has a huge impact on the environment and society, real estate projects are most commonly chosen taking into account only their risk and return, and a very limited number of indices and methods are available… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(16 citation statements)
references
References 100 publications
0
16
0
Order By: Relevance
“…Dobrovolskien et al constructed an evaluation model of real estate sustainability index (resi) at the technical level based on the multi-criteria decision-making method. Experiments show that the model can promote the consideration of sustainable investment in new technologies [4]. Hodoshima et al analyzed the real estate investment trust market in Tokyo based on four performance indicators: internal risk aversion rate (Irra), sharp ratio, Sotino et al found that Irra is more sensitive to potential risks and more relevant to risk averse investors [5].…”
Section: Related Workmentioning
confidence: 99%
“…Dobrovolskien et al constructed an evaluation model of real estate sustainability index (resi) at the technical level based on the multi-criteria decision-making method. Experiments show that the model can promote the consideration of sustainable investment in new technologies [4]. Hodoshima et al analyzed the real estate investment trust market in Tokyo based on four performance indicators: internal risk aversion rate (Irra), sharp ratio, Sotino et al found that Irra is more sensitive to potential risks and more relevant to risk averse investors [5].…”
Section: Related Workmentioning
confidence: 99%
“…As such, despite the view that GBRTs are used to assess sustainability performance, they mostly emphasise environmental performance. Prioritization of an individual sustainability aspect over others invalidates the principles of sustainable development whose aim is to achieve a balance amongst the three pillars [21].…”
Section: Sustainability -The Triple Bottom Linementioning
confidence: 99%
“…For this reason, decision makers can use interval type-2 fuzzy sets. The project environment is particularly vulnerable during conflict [31].…”
Section: Introductionmentioning
confidence: 99%